In situ formation of pH-responsive Prussian blue for photoacoustic imaging and photothermal therapy of cancer. Issue 30 (27th March 2017) - Cheng, Ming; Peng, Wei; Hua, Peng; Chen, Zhengrong; Sheng, Jia; Yang, Juan; Wu, Yongyou
Abstract : Dual pH-responsive theranostic agent reduces the background signal in photoacoustic imaging and non-specific heating of normal tissues in photothermal therapy. Abstract : Designing theranostic agents that are responsive to weakly acidic tumor microenvironments for optimized imaging and therapeutic effects is of great interest in nanomedicine. In the current study, we constructed a pH-triggered smart theranostic system based on pH-responsive Prussian blue, which shows good performance in the photoacoustic imaging (PAI)-guided photothermal therapy (PTT) of tumors. Precursors to Prussian blue, namely ferrous and ferricyanide ions, were separately encapsulated into pH-responsive hydrogels that only degraded under acidic conditions. In vitro results showed that the encapsulated ions were gradually released in acidic buffer, accompanied by hydrogel degradation. After the resultant hydrogel was mixed and intratumorally injected into tumor-bearing mice, the encapsulated ferrous ions and ferricyanide ions were successfully released in the acidic tumor environment, allowing the in situ formation of Prussian blue in the tumor area. This provided an efficient theranostic agent for PAI-guided PTT of cancer. Our research highlights the potential of Prussian blue-based theranostic agents for the precise diagnosis and treatment of cancer.